Corporate Value Creation an Operations Framework for Nonfinancial Managerrs - Lawrence C. Karlson (Wiley, 2015)
orporate Value Creation provides an operations framework that management can use to optimize the impact decisions have on creating value by growing revenue and profitability. Designed to assist professionals without a strong business or financial education, this book provides a thorough understanding of the qualitative and quantitative aspects of managing a business for the purpose of value creation.